Time in Therapeutic Range (TTR) and the Efficacy of Anticoagulant Therapy in Preventing Thromboembolism in Cardiac Patients Receiving Warfarin at Shifa Medical Complex: A Cross-Sectional Study - Habeeb, Mohammed; Hilles, Ashraf (International Journal of Innovative Research in Medical Science, 2021)
Background: Anticoagulant control is assessed by Time in Therapeutic Range (TTR). For a given patient, TTR is defined as the duration of time in which the patient’s International Normalized Ratio (INR) values were within a desired range. Aim: To assess TTR in patients receiving anticoagulant treatment and the efficacy of Anticoagulant therapy in preventing Thromboembolism in Cardiac Patients receiving Warfarin for atrial fibrillation and with high CHADS VASC score, valvular and non-valvular heart disease at a referral center for cardiovascular diseases at Gaza Shifa Medical Complex, Palestine. Materials and Method: Over 8 months, we enrolled eligible patients presenting to Shifa Medical Complex in Gaza for regular INR testing. Demographic data, medical history, and current medications were determined for all participants. TTR was assessed by both tradition and cross-sectional methods. Results: A total of 46 patients (mean age 57.15±12.6 years, 50% women) underwent 230 INR measurements. The mean TTR was calculated as 50.86±21.37%. Participants of this study were assessed for their risk of having stroke using CHADS VASC score and risk of bleeding using HAS BLED score. Risk of stroke was significantly higher for females (P= 0.031). Of the sample patients, 47.8% were in the good control category (TTR >60%), and 52.2% were in the poor control category (TTR <60%). The mean TTR of the studied patients (54.9%) was below the good control range.There were 12 participants had thromboembolism of patients with low traditional TTR. This was statistically significant, TTR with occurrence of thromboembolism, (P= 0.001). Conclusion: We found a mean TTR of 50.86% among study patients diagnosed with atrial fibrillation and high CHADS VASC score, valvular and non - valvular heart disease who were receiving warfarin therapy. None of the risk factor was significantly related to low TTR values among study participants. The study showed the low TTR was associated with increased risk of thromboembolism among participants in this study. Moreover, showed the superiority of tradition TTR over cross-sectional TTR in evaluating anticoagulant therapy.